Food and bioenergy: exploring ideotype traits of a dual-purpose wheat cultivar - Townsend, Toby J.; Roy, Johar; Wilson, Paul; Tucker, Gregory A.; Sparkes, Debbie L. (Elsevier, 2017)
Lignocellulosic biofuels, such as those produced from crop residues, offer the possibility of reducing GHG emissions in the transport sector. Wheat straw is one potential feedstock for these fuels but grain yield has been prioritised over straw yield in crop breeding as straw currently has limited value. Should a new market for straw develop then dual-purpose cultivars (DPCs) that are optimised for food and bioenergy may become desirable. Field experiments were used to assess four key traits – grain yield, straw yield, lodging resistance and straw saccharification potential (i.e. the biofuel yield) – of a selection of modern and older UK wheat cultivars (with release dates ranging from 1964 to 2010) with the aim of identifying dual-purpose cultivars and any trade-offs among the key traits. None of the cultivars assessed were outstanding candidates for use as DPCs. Among the semi-dwarf cultivars there were only minor relationships between traits; including the non-semi-dwarf cultivar showed trade-offs between grain and straw yields. The findings suggest that selecting from among currently grown cultivars offers limited possibility for growing truly DPCs. However, the results indicate that high straw yields can be achieved by selecting high grain-yielding cultivars and managing these to maximise grain yield will also result in high straw yields. Plant growth regulators should continue to be used as these do not significantly reduce straw yields but do decrease lodging susceptibility.